Removal of Mercury from Aqueous Environment by Jute Nanofiber (Journal of Fiber Bioengineering and Informatics, 2013)
The biosorption characteristics of mercury ions from aqueous solution using jute nanofibers, a cellulose-based natural fiber, were explored as a function of pH, nanofiber concentration, contact time andtemperature. Jute nanofibers were obtained after wet milling the jute fibers and subsequently theirmorphology was assessed by various spectroscopy and microscopy techniques. The maximum biosorptioncapacity of the fiber calculated by the Langmuir model was found to be 85.5 mg g^{1.} The adsorptionexperiments revealed that ion-exchange and complexation mechanisms were principal role in thebiosorption process. The present experimental evidence implies that jute nanofibers could be a potentialnatural biomaterial for the removal of environmental contaminations from textile and chemical industries.